LABORATORY CONTROL OF ANTICOAGULANT PROPHYLAXIS IN PREGNANT WOMEN WITH CARDIOVASCULAR DISEASES - V. Medved; T. Savka (World Science, 2021)
This article examines the effect of anticoagulant prophylaxis on pregnancy, childbirth and the postpartum period in women with heart disease. Тhe main mechanisms of formation of side effects from anticoagulant prophylaxis in pregnant women with diseases of the cardiovascular system were studied by means of laboratory research methods,. Have been studied the effects and interaction of different types of anticoagulant prophylaxis and aspirin prophylaxis on primary hemostasis. An algorithm for diagnosing the negative effect of anticoagulants on platelets has been developed. The study examines the possibility of drug correction of the development of side effects from anticoagulant thromboprophylaxis for women with diseases of the cardiovascular system.